Batik Motifs in Conserving Regional Potentials and Indonesian Local Wisdom - Farihah Farihah; Halimul Bahri; Dina Ampera; Nurhayati Tanjung; Yudhistira Anggraini (Journal of Innovation in Educational and Cultural Research, 2024)
Many Batik motifs in North Sumatra are adopted from the decorative motifs of the Batak tribe. The Malay tribe is a symbol of the city of Medan, which has an attractive variety of decorations. This research aims to produce Malay batik motif designs and carry out batik trials on fabric with motifs that have been developed. This research uses the IDI development model. The result of validating the motif design aspect is 0.83, and the motif appearance aspect is 0.88. The functional aspect assessment resulted in a score of 0.87. The assessment result of the color aspect obtained a score of 0.87, and the balance aspect of batik design motifs obtained a score of 0.79. The validation results conclude that the developed batik motif is declared suitable for use in producing textile products in Malay batik. The results of the development of Malay batik can increase its diversity, potentially advancing local culture in the fashion world.